The Virtual Manifestation of Indifference: The Normalization of Cancel Culture as Offensive Humor on Social Media - Eşidir, Osman Vedüd; Bak, Gökhan; Altıntop, Mevlüt (Ebru Bagci, 2025)
Social media has evolved beyond merely influencing everyday life to become an indispensable part of the social fabric. Similar to real life, human emotions and behaviors such as happiness, enthusiasm, love, anger, hatred, sadness, pain, and peace emerge within social media environments, and these emotions collectively create a new ecosystem and culture. An important element of this new culture is the phenomenon of “lynch” (mob) culture, which also finds its place on social media. This study examines the lynch culture on social media, focusing specifically on Platform X. Following the announcement of the 2025 Higher Education Institutions Exam (YKS) results, posts related to a student who ranked first in Turkey in the equal-weight and verbal fields were analyzed. The analysis yielded three main findings: First, the subject was completely detached from its original context. Second, the student’s image and mode of communication were used manipulatively and disrespectfully toward personal rights within social media interactions. Third, it demonstrated how insensitive, ruthless, and malevolent the lynch culture—also referred to as “offensive humor” and emerging as a product of popular culture on social media—truly is. This study contributes important awareness and insights regarding lynch culture in the new media environment. © 2025, Ebru Bagci. All rights reserved.
Keywords: Cancel Culture; Digital Lynching; Offensive Humor; Online Hate Speech; Social Media